Evaluation of Heavy Metal Status, Quality and Safety of Vegetables Sold in Markets Located in Makurdi Metropolis, Nigeria for Human Consumption - Anjembe, Bemgba; Tyavkase, Nguveren (International Journal For Research In Agricultural And Food Science, 2021)
Studies were carried out to evaluate the quality of some common vegetables sold in markets located within Markurdi metropolis in terms of their heavy metal status and safety for human consumption. Five markets (Makurdi Modern Market, Wadata, High Level, Wurukum and North bank) where vegetables are sold in large quantities were selected. Four common vegetables sold and consumed in very large quantities were sampled for twelve weeks. The vegetables include Cabbage, Pumpkin, Okra and Amaranthus. Collected samples were subjected to Laboratory Analysis and concentrations of five heavy metals were determined. These metals were Zinc, Copper, Lead and Selenium. These concentrations were compared with the FAO/WHO safety limits for heavy metals in vegetables and food. It was observed that metal concentration in the samples were lower than the safety limits of FAO/WHO and are thus safe for human consumption. Concentration of the metals in Cabbage was consistently higher than the other vegetables while the concentration in Amaranthus was mostly lower across the selected Markets. Samples from North Bank market had considerably lower concentration of these metals while samples from High level market contained the highest concentration. It was concluded that Amaranthus from North Bank market is of best quality for human consumption. Monitoring of heavy metal concentration in vegetables sold in these markets would be necessary as these vegetables have the capacity to phytoremedy contaminated substrates. This is necessary for preservation of human health and environmental protection.